Explorations of the chemical constitution and aqueous solution status of caries-arresting silver(I)-diammine fluoride and silver(I)-fluoride products using high-resolution 19F NMR analysis. Spectroscopic and SEM investigations of their interactions with human saliva: evidence for the in vivo salivary-catalysed autoconstruction of Ag/AgCl-based nanoparticles (IV-SCAN)—part I - Hunwin, Kayleigh; Page, Georgina; Edgar, Mark; Botana, Adolfo; Armitage, Rachel; Bhogadia, Mohammed; Desai, Unmesh; Duffin, Steven; Duffin, Marcus; Chan, Wyman; Grootveld, Martin (Frontiers in Oral Health, 2024)
Silver(I)-diammine fluoride (SDF) and silver(I)-fluoride (SF) complexes have been successfully employed for the arrest of dental caries for many years. However, to date there are very few studies available reporting on the molecular structural compositional and solution status of these agents (typically applied as highly-concentrated 38%(w/v) solutions). Here, we explored the solution status and chemical constitution of commercially-available SDF and SF products, and secondly investigated the multicomponent interplay of these products with biomolecules present in intact human whole-mouth salivary supernatants (WMSSs) in vitro. High-resolution 19 F NMR analysis was employed to explore SDF and SF product solutions, and to determine WMSS fluoride (F -) concentrations, whereas ammonia (NH3) release form SDF was tracked by 1 H NMR spectroscopy. SEM and thin-film FTIR-ATR analyses were employed to explore the atomic and molecular compositions of sequentially-generated AgCl deposits and chromophoric Ag/AgCl nanoparticles (CSNPs); the time-dependent generation of the latter was followed spectrophotometrically. 19 F NMR spectra of aqueous SF solutions contained a very broad F -signal (Δv1/2 70 Hz), demonstrating that much of its solvated F -content was rapidly exchanging with Ag(I) on the NMR timescale, but those of SDF had a much sharper resonance, similar to that of 'free' F -(4 Hz). Moreover, further NMR results revealed that a popular SDF product contained high molar excesses of both F -and NH3. Treatment of WMSSs with SDF and SF generated an off-white precipitate, which slowly developed into CSNPs at 23 o C; SEM demonstrated high contents of both silver and chloride in this material (ca.1:1 atomic content ratio). FTIR-ATR analysis demonstrated that the CNPs formed contained a range of salivary biomolecules, which appear to encapsulate the Ag/AgCl core (significant thiocyanate contents were also found). In conclusion, NMR results acquired demonstrated that SF, but not SDF, product solutions feature rapidly-exchanging F -between its 'free' and Ag(I)-bound forms, and that SDF contains large excesses of both F -and its NH3 ligands. Characterised AgCl deposits and CSNPs were sequentially produced from the interactions of these complexes with WMSS biomolecules. The observed autobioconstruction of CSNPs with potential cariostatic and microbicidal properties is of much therapeutic significance.